The Effect of Information Technology Misuse, Learning Motivation and Level of Religiosity on Academic Fraud Behavior of Accounting Students as Prospective Accountants (Studies at Islamic-Based and National Private Universities) - Ismaya Nur Zannah; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of misuse of information technology, learning motivation and level of religiosity on the academic cheating behavior of accounting students as prospective accountants at Islamic-Based and National Private Universities. This study uses quantitative methods with primary data, by distributing questionnaires. The population in this study was students of accounting study program at Muhammadiyah University of Sidoarjo as an Islamic-based university and at Hayam Wuruk Perbanas University Surabaya as a national private-based university. The sampling technique used purposive sampling with multiple linear regression analysis, t test, independent sample t-test as a data analysis technique. The results of this study are the misuse of information technology and the level of religiosity affect the academic cheating behavior of accounting students as prospective accountants, learning motivation has no effect on the academic cheating behavior of accounting students as prospective accountants, there are differences in academic cheating behavior that occurs in Islamic-based and National Private Universities.